A comparison between the effect of systemic and coated drug delivery in osteoporotic bone after dental implantation. (September 2022) - Ashrafi, Mehran; Gholamian, Farzaneh; Doblare, Manuel
Highlights: The effect of Zoledronate on the RANK/RANK-L/OPG pathway in bone remodeling is here investigated with a pharmacokinetic model and a finite element approach. A chemo-mechano-biological bone remodeling model coupled with a pharmacokinetic one is used to evaluate the effects of systematic and local drug delivery on the bone around the dental implant. For local drug delivery, Fickean diffusion is used to compute the drug concentration distribution in bone around the dental implant. Systematic drug delivery affects the whole skeleton, while local drug delivery affects only the area around the dental implant. Local drug delivery reduces the side effects produced by systemic drug administration like increasing bone brittleness and damage far from the implant. Abstract: The increased life expectancy has boomed the demand of dental implants in the elderly. As a consequence, considering the effect of poorer bone quality, due to aging or associated diseases such as osteoporosis, on the success of dental restoration is becoming increasingly important. Bisphosphonates are one of the most used drugs to overcome the effect of osteoporosis as they increase bone density. Bisphosphonates modify the physiological bone remodeling process by adhering to the bone surface, reducing the activity of osteoclasts. This study aims at comparing the effect on bone remodeling of two drug delivery methods of Bisphosphonates: local delivery by coating the implant surface and systemic delivery. A chemo-mechano-biological bone remodeling model validated in a previous paper was used here. The two drug delivery schemes were modeled by means of a finite element approach. In the systemic drug delivery case, the amount of drug that reaches the bone compartment was calculated using a pharmacokinetic model while in the local drug delivery system, the dose was calculated using Fickean diffusion. In particular, the effect of Zoledronate is studied here. The two drug delivery approaches are compared between them and with a control case with no drug. The results show that the use of Bisphosphonates increases the mechanical strength of bone, thus improving the implant fixation along time. Systemic drug delivery affects the entire skeleton, while local drug delivery only affects the area around the dental implant, which reduces the side effects of Bisphosphonates, such as increasing the mineral content, which may promote bone brittleness and microdamage far from the implant. These results support the conclusion that dental implants coated with Bisphosphonates can be a good solution for osteoporotic or low bone density patients without the long-term side effects of systemic drug delivery.